Effect of Red Clover Isoflavones over Skin, Appendages, and Mucosal Status in Postmenopausal Women - Markus Lipovac; Peter Chedraui; Christine Gruenhut; Anca Gocan; Christine Kurz; Benedikt Neuber; Martin Imhof (Hindawi Limited, 2011)
Objective. Evaluate in postmenopausal women the effect of red clover extract (RCE) isoflavones over subjective status of skin, appendages, and several mucosal sites. Method. Postmenopausal women (n=109) were randomly assigned to receive either two daily capsules of the active compound (80 mg RCE, Group A) or placebo of equal appearance (Group B) for a 90-day period. After a washout period of 7 days, medication was crossed over and taken for 90 days more. Subjective improvement of skin, appendages, and several mucosal site status was assessed for each studied group at 90 and 187 days using a visual analogue scale (VAS). In addition, libido, tiredness, and urinary, sleep, and mood complaints were also evaluated. Results. Women after RCE intervention (both groups) reported better subjective improvement of scalp hair and skin status, libido, mood, sleep, and tiredness. Improvement of urinary complaints, nail, body hair, and mucosa (oral, nasal, and ocular) status did not differ between treatment phases (intra- and intergroup). Overall satisfaction with treatment was reported higher after RCE intervention (both groups) as compared to placebo. Conclusion. RCE supplementation exerted a subject improvement of scalp hair and skin status as well as libido, mood, sleep, and tiredness in postmenopausal women.